(untitled) (International Journal of Environmental Sciences, 2025)
This subject study become carried out at the Botanical Garden of the Department of Life Sciences, College of Basic Education, Al-Mustansiriya University, throughout the winter developing season of 2024-2025. The goal changed into to explore how varying concentrations of the increase regulator gibberellic acid (GA) and potassium fertilizer, as well as their interaction, impact the phenotypic and floral characteristics of celebrity anise (Pimpinella anisum (L.). Anise seeds had been planted on November 1, 2024, with potassium tiers set at 0, 100, and 200 kilograms according to hectare (kg·ha⁻¹) introduced to the soil. Additionally, flowers had been handled with gibberellic acid at concentrations of 0, 50, and 100 mg/L⁻¹. The look at became designed the usage of a randomized complete block design, offering three replicates and a factorial format (3x3x3) that blanketed 27 experimental units, every measuring 1 x 1 square meter. Throughout the examine, ordinary monitoring changed into performed to carry out crucial soil and crop management duties along with irrigation, weed control, and fertilization. Spraying gibberellin at a attention of 50 mg/L⁻¹ led to fantastic increases: the quantity of branches rose with the aid of 32.99%, dry weight accelerated with the aid of 46.04%, and the quantity of fundamental inflorescences in line with plant grew with the aid of 30.69%, compared to the manage remedy. When 100 kg/ha⁻¹ of potassium was applied, the results showed an increase in branches by 22.58%, dry weight by 26.52%, the number of main inflorescences by 12.46%, and flowers per main inflorescence by 11.00%, again in comparison to the control treatment. Furthermore, the combination of gibberellic acid and potassium had a substantial impact on several traits. Specifically, the interaction between a concentration of 50 mg/L⁻¹ of gibberellic acid and 200 kg/ha⁻¹ of potassium resulted in remarkable improvements: plant height increased by 58.01%, the number of branches surged by 65.74, and dry weight jumped by 84.42%, all in contrast to the control treatment.